Persepsi Masyarakat Seni Terhadap Karya Mural Methodos - Imam Fathurahman (AKSA: Jurnal Desain Komunikasi Visual, 2019)
This mural research aims to find out how people recognize the identity of their artists from the experiences and opinions of the public when viewing and reading mural works that are in the public room. The object of the mural that the researchers chose was Methodos's mural on the wall of one of the food stalls located in Mrisen Village, RT. 007, Panggungharjo Village, Sewon District, Bantul, Yogyakarta. This study uses qualitative research and interview methods to find information from the experience of the arts community on mural art.